Status Kesehatan Gingiva Terhadap Kebiasaan Menyikat Gigi dan yang Tidak Menyikat Gigi di Malam Hari Pada Anak SD Inpres Unggulan BTN PEMDA Usia 10-12 Tahun - Thioritz, Ernie; Hamid, Ellis Mirawati; Aminah, Sitti (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2023)
Dental and oral health should be taken care of from an early age, as dental condition can affect dental health in adulthood. Our gums can get damaged if we don't brush our teeth often, especially before going to bed. Gingiva is a part of the mucous membrane of the mouth that surrounds the tooth neck and covers an ungrown crown. It serves as a structural support for the surrounding tissue. The study investigated the relationship between the health status of the gums and the habit of brushing teeth at night in children aged 10-12 years. This research uses quantitative research with analytical observational design and a purposive sampling approach which means that samples are determined with certain considerations or have criteria to be met. The study involved 143 students aged between 10 and 12 at SD Inpres Unggulan BTN Pemda, with 66 samples. The results showed that 34 people (51.5%) brushed their teeth at night, while 32 people (48.5%) did not. Among the children who brushed their teeth at night, five (7.6%) had healthy gums, 28 (42.4%) had mild inflammation, and one (1.5%) had moderate inflammations. Among children who didn't brush their tooth at night there were none of them having a healthy gum, 24 (36.4%) experienced mild inflamation. The results of statistical research show that p 0.05 is 0.005. So, there's a significant link between the habit of brushing teeth at night and the health of the gums.